The Clinical Profile, Early Warning Score, and Outcome of Children Aged 0–12 Years Referred to a Tertiary Care Hospital in North India - Eswaramoorthy, Brinda; Gupta, Ratan; Bhatt, Meenakshi; Roy, Manas Pratim (Journal of Child Science, 2021)
Pediatric patients are referred for multiple reasons, either for better therapeutic services or diagnostic purposes. The clinical condition of patients at the time of referral can significantly affect the outcome of such patients and there is not much data on this aspect. The overall objective of this study was to study the demographic and clinical profile, the causes for referral, and the outcome of pediatric patients being referred to a single tertiary care hospital. This was a prospective observational study done in the Department of Pediatrics of a single tertiary care hospital in North India over the course of 1 year. Patients referred from other health facilities in the age group 0 to 12 years who were admitted in the pediatric ward of the hospital were enrolled. The primary objective was to study the clinical profile and outcome (mortality) of these patients. The secondary objectives were to study the referral pattern of the referred patients, causes for referral, and the severity of illness at the time of admission as assessed by Irish Pediatric Early Warning Score (PEWS) and its correlation with the outcome. The outcomes were categorized as: discharge, death, left against medical advice, referred to other centers, others. Early warning scores are useful to measure the severity of disease and to follow patients' progress. The Irish PEWS score was used in this study to provide a rapid measure of the degree of sickness. Respiratory system disorders and neonatal illnesses were the most common illnesses observed. Most patients had low disease severity as per Irish PEWS score. The overall mortality rate among the referred patients was 19.25%. Patients with younger age, higher scores, neonatal illnesses, and neurological disorders had higher risk of mortality. Training of health personnel at primary and secondary levels in the commonly encountered illnesses will improve provision of care at the local level and decrease low risk referrals.
Keywords: referral; Irish PEWS; pediatric; mortality